1999
DOI: 10.1046/j.1524-475x.1999.00442.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the acute and chronic wound environments: the role of proteases and their inhibitors

Abstract: To assess the differences in proteolytic activity of acute and chronic wound environments, wound fluids were collected from acute surgical wounds (22 samples) and chronic wounds (25 samples) of various etiologies, including mixed vessel disease ulcers, decubiti and diabetic foot ulcers. Matrix metalloproteinase (MMP) activity measured using the Azocoll assay was significantly elevated by 30 fold in chronic wounds (median 22.8 microg MMP Eq/ml) compared to acute wounds (median 0.76 microg MMP Eq/ml) (p < 0.001)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
631
2
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 788 publications
(674 citation statements)
references
References 36 publications
18
631
2
7
Order By: Relevance
“…Studies have also shown that the prolonged exposure of wound tissues to pro-inflammatory cytokines, for example, interleukin and tumor necrosis factor-α, may act to stimulate the production of MMPs, while inhibiting the synthesis of tissue inhibitors of metalloproteinases. 31 Furthermore, MCP-1 has recently been shown to up-regulate MMP-1 and MMP-2 mRNA expression in human skin fibroblasts in which interleukin-1α has been found to take part as a mediator through an autocrine loop. 32 As a matter of fact, curcumin itself possesses distinct chemical properties that allow it to use the metal atoms of metalloproteins as a means to interact with these proteins and become a natural MMP inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that the prolonged exposure of wound tissues to pro-inflammatory cytokines, for example, interleukin and tumor necrosis factor-α, may act to stimulate the production of MMPs, while inhibiting the synthesis of tissue inhibitors of metalloproteinases. 31 Furthermore, MCP-1 has recently been shown to up-regulate MMP-1 and MMP-2 mRNA expression in human skin fibroblasts in which interleukin-1α has been found to take part as a mediator through an autocrine loop. 32 As a matter of fact, curcumin itself possesses distinct chemical properties that allow it to use the metal atoms of metalloproteins as a means to interact with these proteins and become a natural MMP inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…It has been speculated that topical application of these agents, especially in the harsh microenvironment of a chronic wound, is fraught with problems. There are questions about the appropriate topical dose and the delivery vehicle, penetration of the polypeptide into the ulcer bed and its breakdown by tissue metalloproteinases (Robson et al, 1998;Trengove et al, 1999;Lobmann et al, 2002). Also, single growth factors may not be enough (Robson et al, 2000;Smith et al, 2000a,b).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of venous ulcers, a number of hypotheses have been proposed. Some of these hypotheses have emphasized failure of the fibrinolytic system and the formation of pericapillary fibrin cuffs (Browse and Burnand, 1982;Van de Scheur and Falanga, 1997), while others have addressed the possibility of trapping of growth factors (Falanga and Eaglstein, 1993) and breakdown of extracellular matrix and cytokines by excessive amounts of tissue metalloproteinases (Trengove et al, 1999;Lobmann et al, 2002). More recently, however, a novel line of investigation has been centered on the hypothesis that chronic wounds fail to heal because their resident cells are senescent and/or have become unresponsive to the action of growth factors.…”
mentioning
confidence: 99%
“…This would suggest that exogenous presentation can lead to clearance, sequestration [41] or destruction [42] of the factor.…”
Section: Discussionmentioning
confidence: 99%